2022
DOI: 10.1002/ijgo.14079
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for abortion‐related complications: Insights from the WHO Multi‐Country Survey on Abortion‐related Morbidity across 11 African countries

Abstract: SynopsisA collection of seven papers from the WHO Multi‐Country Survey on Abortion‐related morbidity (MCS‐A) using secondary data analysis to assess the quality of care for abortion‐related complications in facilities in Sub‐Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This gap in evidence exacerbates its invisibility, limiting its recognition as a health issue to be addressed. As a result, evidence about abortion in fragile and conflict-affected settings was identified by researchers, practitioners [ 27 29 ] and WHO [ 30 ] as a priority research topic.…”
Section: Introductionmentioning
confidence: 99%
“…This gap in evidence exacerbates its invisibility, limiting its recognition as a health issue to be addressed. As a result, evidence about abortion in fragile and conflict-affected settings was identified by researchers, practitioners [ 27 29 ] and WHO [ 30 ] as a priority research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have elucidated the relationship between low quality of care with high levels of abortion stigma and increased abortion-related morbidity and mortality, indicating that quality improvement interventions are important for reducing community stigma and improving health outcomes (25)(26)(27).…”
Section: Quality Of Abortion Carementioning
confidence: 99%
“…Unfortunately, a comprehensive review of person-centered abortion care from diverse country settings found that health facilities and providers often fail in providing adequate person-centered care to CAC clients (35). This results in devastating impacts for those seeking induced abortion or PAC, including negative mental health and psycho-social outcomes, delayed care-seeking, and using unsafe methods to avoid going to health facilities (26,27,35).…”
Section: Quality Of Abortion Carementioning
confidence: 99%
See 1 more Smart Citation
“…This gap in evidence exacerbates its invisibility, limiting its recognition as a health issue to be addressed. As a result, evidence about abortion in fragile and conflict-affected settings was identified by researchers, practitioners [27][28][29] and WHO [30] as a priority research topic.…”
Section: Introductionmentioning
confidence: 99%